Prediabetes is associated with a higher serum neurofilament light chain level in adolescents - Chen, Zheng; Wu, Lan-Ping; Peng, Tuo-Chao (Frontiers in Endocrinology, 2023)
Objective Serum neurofilament light chain (sNfL) level, which is a biomarker indicative of neuroaxonal damage and cognitive impairment, has been reported in several neurological diseases. There has been a lack of studies on the association between sNfL levels and prediabetes in adolescents. This study investigated whether sNfL levels were higher in adolescents with prediabetes undergoing elective orthopedic surgery. Methods The sNfL level was measured in 149 adolescents aged from 12 to 18 years who underwent elective orthopedic surgery at the Hunan Children’s Hospital (18 with and 131 without prediabetes). We evaluated the association between prediabetes and sNfL level after adjusting for age, sex, and triglycerides using a multivariable linear regression model. Results The prevalence of prediabetes in adolescents was 12.08%. Univariate logistic regression analysis showed that prediabetes was related to sNfL. In multivariate logistic regression analysis, the association between prediabetes with sNfL levels remained significant after adjustment for age, sex, and triglyceride. The relationship between the two was further visualized by a smoothed curve. Conclusions Prediabetes is associated with a higher sNfL. Further large-scale and prospective studies are needed to verify the clinical application of sNfL as a monitoring biomarker for adolescent prediabetes in adolescents and to evaluate the performance of sNfL in predicting the incidence of neuropathy and cognitive dysfunction in adolescents with prediabetes.